2023
DOI: 10.21435/tl.284
|View full text |Cite
|
Sign up to set email alerts
|

Miten tutkia kohteliaisuutta? Käsityksiä suomalaisesta ja ranskalaisesta kohteliaisuudesta

Johanna Isosävi

Abstract: How to study politeness? Perceptions of Finnish and French politeness Politeness is a key means by which we maintain interpersonal relationships. This book is the first comprehensive study of politeness in Finnish. Based on linguistic and pragmatic research, the book spans three parts. The first part is theoretical and historical, summarising three waves of politeness research, describing politeness as a cultural and historical phenomenon. The second part is empirical, providing an example of the study of im/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…As conventionalisation relates to pragmatic competence, second language speakers may not know what type of behaviour is conventionalised in a specific context (House and Kádár, 2021: 35). My studies showed that when arriving in the target culture and not necessarily speaking the target language, cultural outsiders observed differences related to non-verbal politeness, such as holding doors open for others or not (Isosävi, 2020a;2023b). After spending time in the target culture, cultural outsiders reported adapting to politeness norms, such as greeting less (French participants) or more (Finnish participants), in order to avoid a marked behaviour judged as impolite (Isosävi, 2020b;2023b).…”
Section: 1mentioning
confidence: 90%
See 2 more Smart Citations
“…As conventionalisation relates to pragmatic competence, second language speakers may not know what type of behaviour is conventionalised in a specific context (House and Kádár, 2021: 35). My studies showed that when arriving in the target culture and not necessarily speaking the target language, cultural outsiders observed differences related to non-verbal politeness, such as holding doors open for others or not (Isosävi, 2020a;2023b). After spending time in the target culture, cultural outsiders reported adapting to politeness norms, such as greeting less (French participants) or more (Finnish participants), in order to avoid a marked behaviour judged as impolite (Isosävi, 2020b;2023b).…”
Section: 1mentioning
confidence: 90%
“…Yet, her experiences on finger pointing as a marked behaviour contributed to a change in her behaviour (cf. also Isosävi, 2023b) We cannot influence the skills of our interlocutor. We shouldn't make evaluations regarding why we behave a certain way.…”
Section: Many Of Usmentioning
confidence: 96%
See 1 more Smart Citation